Trade-off between tree planting and wetland conservation in China - Yi Xi; Shushi Peng; Gang Liu; Agnès Ducharne; Philippe Ciais; Catherine Prigent; Xinyu Li; Xutao Tang (Nature Communications, 2022)
Afforestation and reforestation programs aimed at enhancing carbon sequestration may have unintended effects on non-forest ecosystems and biodiversity. Here the authors use remote sensing and land surface modelling to quantify trade-offs between tree planting and wetland conservation in China